Fiber-reinforced wave-absorbing patch as well as preparation method and application thereof

By adopting a three-layer structure fiber-reinforced wave absorbing patch, combined with the design of impregnated mesh fibers and single-layer wave absorbing patches, the problems of existing wave absorbing materials in terms of density, frequency band and cost are solved, and high efficiency is achieved The electromagnetic wave absorption and mechanical properties are improved, suitable for a variety of application scenarios.

CN119133877AInactive Publication Date: 2024-12-13NINGBO INNOVATION CENT FOR APPLIED MAGNETICS CO LTD

Patent Information

Application Number
CN202411614695.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In practical applications, existing absorbent materials face problems such as high density, fragility, limited single frequency band, poor environmental stability and high processing costs, making it difficult to realize fiber-reinforced absorbent patches with excellent absorbent properties and mechanical properties.

Method used

A fiber-reinforced wave absorbing patch with a three-layer structure, the intermediate layer is a glue-immersed mesh fiber. The surface is made of a mesh by stacking hot pressing. Combining different materials and impregnated materials, the thickness and mesh design are adjusted. To achieve coordination of absorbing properties and mechanical properties, simplify the preparation process.

Benefits of technology

It improves the tensile strength and electromagnetic wave absorption capacity of the fiber-reinforced wave absorbing patch, reduces costs, and is suitable for compact thin-layer design in different fields, achieving a perfect integration of wave absorption, mechanical properties and practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133877A_ABST
    Figure CN119133877A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced wave-absorbing patch and a preparation method and application thereof, the wave-absorbing patch comprises a three-layer structure, the middle layer is impregnated reticular fiber as a reinforcing matrix, the upper layer and the lower layer are single-layer wave-absorbing patches, and the fiber-reinforced wave-absorbing patch with a latticed surface is prepared after lamination and hot pressing. A wave-absorbing agent adopted in the fiber-reinforced wave-absorbing patch comprises at least one of carbonyl iron, iron-silicon-chromium, iron-silicon-aluminum, iron-nickel, cobalt-based amorphous wires and iron-based amorphous powder. The invention provides a novel wave-absorbing solution with excellent electromagnetic wave-absorbing performance, mechanical strength and good processing adaptability, and the prepared fiber-reinforced wave-absorbing patch integrates an advanced wave-absorbing material technology and a fiber-reinforced composite structure design. The device is specially used for suppressing electromagnetic radiation, improving electromagnetic compatibility and protecting electronic equipment from electromagnetic interference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing absorbing materials, and in particular relates to a fiber-reinforced absorbing patch and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern science and technology, especially the widespread application of electronic equipment, communication systems, radar facilities and various wireless technologies, the electromagnetic radiation brought about is also increasing, forming serious electromagnetic environmental pollution. These electromagnetic waves may not only have potential effects on human health, but also interfere with the normal operation of electronic equipment, or even have more serious effects. Therefore, the development of effective electromagnetic wave absorbing materials to attenuate, suppress or shield unnecessary electromagnetic radiation has become a technical problem that needs to be solved urgently.

[0003] Traditional absorbing materials mainly include ferrites, carbon-based materials, conductive polymers, etc. They can absorb electromagnetic waves to a certain extent and reduce electromagnetic wave reflection and propagation through magnetic loss, dielectric loss or composite loss mechanisms. However, these materials often face many challenges in practical applications. For example, although ferrite materials have good absorbing performance, they are dense and fragile, which is not conducive to lightweight design and processing; although carbon-based materials are light and conductive, the absorbing frequency band of a single material is limited, making it difficult to achieve broadband and efficient absorption; conductive polymers may be limited in their wide application due to poor environmental stability and high processing costs.

[0004] To overcome these limitations, researchers began to explore the development of fiber-reinforced absorbing materials. This type of material aims to combine the excellent mechanical properties of fiber materials such as high strength, light weight, and fatigue resistance with the electromagnetic loss characteristics of the absorbing medium to achieve synergistic optimization of performance. Fiber-reinforced absorbing materials can not only effectively improve the overall mechanical properties of the material, making it more durable and reliable in practical applications, but also broaden the absorbing frequency band and improve the absorbing efficiency through reasonable structural design, such as multi-layer composite and gradient distribution.

[0005] However, the research and development of fiber-reinforced absorbing patches is not an easy task. At present, fiber-reinforced absorbing patches are still in the research and development stage. Due to their complex structure, complex processing technology, difficult preparation and high cost, they must ensure that the material has efficient electromagnetic wave absorption ability, and maintain good mechanical properties to avoid failure due to stress in practical applications, and meet the needs of compact thin-layer design in different fields. In-depth research is needed in material design, preparation technology and performance optimization.

[0006] Therefore, in order to focus on overcoming the limitations of existing technologies, it is necessary to study an absorbing patch with a simple preparation method, thin layer, excellent absorbing performance and mechanical strength. Through material design, optimization of preparation process and improvement of performance evaluation system, a perfect combination of absorbing performance, mechanical properties and practicality can be achieved to meet the needs of different fields for high-performance absorbing materials and contribute to building a safer and more efficient electromagnetic environment. Summary of the invention

[0007] In view of the above, the purpose of the present invention is to provide a fiber-reinforced absorbing patch and a preparation method and application thereof. The fiber-reinforced absorbing patch combines the high-strength mechanical properties of the fiber mesh structure and the electromagnetic wave absorption performance of the absorbing patch, aiming to provide a composite material with both excellent mechanical properties and electromagnetic wave absorption capacity, while simplifying the preparation process to improve production efficiency.

[0008] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows: In the first aspect, an embodiment of the present invention provides a fiber-reinforced absorbing patch, which includes a three-layer structure, with a middle layer of impregnated mesh fibers as a reinforcing matrix, and the upper and lower layers are single-layer absorbing patches, which are laminated and hot-pressed to form a fiber-reinforced absorbing patch with a grid-like surface, wherein the middle layer of impregnated mesh fibers is a mesh cloth made of fibers with a through-hole grid shape, which is prepared after impregnation.

[0009] Preferably, the intermediate layer of dipped mesh fibers is in a cloth-like shape with a thickness of 0.1 to 0.6 mm. This thickness can ensure that the intermediate layer of dipped mesh fibers is less likely to deform, tear or wear, and has both wave-absorbing performance and excellent mechanical properties. The wave-absorbing performance and mechanical properties can be regulated by adjusting the thickness, and the thickness can be reduced according to actual needs to save raw material costs.

[0010] Preferably, the mesh shape of the intermediate layer of impregnated mesh fibers is a periodically arranged prismatic, triangular or hexagonal mesh. Further preferably, a hexagonal mesh is used, and the spacing between opposite sides is 0.3 to 5 mm. The use of a hexagonal mesh can ensure uniform resistance to stress changes during application. Selecting the spacing between opposite sides in this range can flexibly adjust the mesh size of the mesh fiber, achieve flexible adjustment of the wave absorption performance and mechanical properties, and further broaden the application scenarios.

[0011] Preferably, the material of the intermediate layer of impregnated mesh fibers includes at least one of nylon, polyester, cotton, aramid, ultra-high molecular weight polyethylene, carbon fiber, stainless steel, nickel, and copper. The material of the mesh fibers directly affects the mechanical properties of the prepared fiber-reinforced absorbing patch, and the selection of these materials can ultimately ensure that the tensile strength of the fiber-reinforced absorbing patch is not less than 4MPa.

[0012] Preferably, the dipping material of the intermediate layer of dipping mesh fibers is a wave-absorbing slurry, and the wave-absorbing slurry is compounded with a binder and a wave-absorbing agent.

[0013] The material of the adhesive will affect the fusion amount of the absorber. Preferably, the adhesive includes at least one of silicone, polyurethane, epoxy resin, acrylic acid, and phenolic resin.

[0014] The material and content of the absorber directly affect the absorbing performance. In order to achieve 1-18Ghz absorbing performance, preferably, the absorber includes at least one of carbonyl iron, iron silicon chromium, iron silicon aluminum, iron nickel, cobalt-based amorphous wire, and iron-based amorphous powder, and the added mass of the absorber is 80% to 90%.

[0015] Preferably, the intermediate layer of impregnated mesh fibers is completely immersed in the absorbing slurry, vacuum-immersed in a vacuum device for 1 hour, then fished out, and excess slurry is squeezed out by double rollers, and then the residual slurry is blown away with a hair dryer to ensure that the meshes of the mesh fibers after impregnation are all through holes, thereby ensuring the bonding between the upper and lower single-layer absorbing patches.

[0016] Preferably, the single-layer absorbing patch is prepared by a casting process, with acrylic double-sided adhesive on the back, and the total thickness is 0.25mm to 1.5mm. Combining the mesh microstructure design of the intermediate layer of impregnated mesh fibers with the different thickness combinations of the single-layer absorbing patch can enhance the multiple scattering and absorption of electromagnetic waves, which helps to achieve more accurate electromagnetic response regulation.

[0017] In a second aspect, an embodiment of the present invention provides a method for preparing a fiber-reinforced absorbing patch, comprising the following steps: Preparation of microwave absorbing slurry: Compound the binder and the microwave absorbing agent, wherein the added mass of the microwave absorbing agent is 80% to 90%; Preparation of the intermediate layer of dipped mesh fiber: the mesh fiber is mixed with the microwave absorbing slurry, and then impregnated, rolled, blown and cured to form the dipped mesh fiber; Preparation of single-layer absorbing patch: silica gel is mixed with at least one of carbonyl iron, iron silicon chromium, iron silicon aluminum, iron nickel, cobalt-based amorphous wire, and iron-based amorphous powder, and a single-layer absorbing patch is made after casting and heat curing, and double-sided tape is pasted on the back of the patch; Preparation of fiber-reinforced absorbing patch: The dipped mesh fiber is used as the middle layer, and the upper and lower layers are single-layer absorbing patches. The single-layer absorbing patch is bonded to the middle layer of dipped mesh fiber through double-sided tape. After lamination and hot pressing, a fiber-reinforced absorbing patch with a grid-like surface is made.

[0018] In a third aspect, an embodiment of the present invention provides an application of a fiber-reinforced absorbing patch in radar stealth, equipment electromagnetic wave absorption and anti-electronic interference, including: using the above-mentioned fiber-reinforced absorbing patch for radar stealth, equipment electromagnetic wave absorption and anti-electronic interference.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The fiber-reinforced absorbing patch provided by the present invention uses an intermediate layer of impregnated mesh fibers as a reinforcing matrix. Compared with traditional absorbing patches, it has higher tensile strength and is less prone to deformation, tearing or wear. It is suitable for occasions that need to withstand mechanical stress, vibration or impact.

[0020] (2) The fiber-reinforced absorbing patch provided by the present invention has a multi-layer structure. Through the mesh microstructure design of the intermediate layer of impregnated mesh fibers and the combination of different thicknesses of the single-layer absorbing patch, the multiple scattering and absorption of electromagnetic waves are further enhanced, and more precise electromagnetic response regulation is achieved, which is superior to general-purpose or single-function absorbing materials.

[0021] (3) The preparation process of the fiber-reinforced absorbing patch provided by the present invention is simple, which helps to improve production efficiency and can be continuously produced on the basis of the traditional absorbing patch production process, thus having high industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 is a schematic diagram of the layered structure of a fiber-reinforced absorbing patch provided in an embodiment of the present invention; Figure 2 is a flow chart of a method for preparing a fiber-reinforced absorbing patch provided by an embodiment of the present invention; Figure 3 This is a physical sample picture of the fiber-reinforced absorbing patch provided in Example 1 of the present invention; Figure 4 RL curves of Example 1 of the present invention and Comparative Example 1; Figure 5 3 is the reflection loss RL curve of Examples 2, 3, 4 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0024] To make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.

[0025] The inventive concept of the present invention is: in view of the fact that the fiber-reinforced absorbing patch in the prior art is still in the research and development stage, and the mechanical and absorbing performances still need to be strengthened, the embodiment of the present invention provides a fiber-reinforced absorbing patch and its preparation method and application, which integrates advanced absorbing material technology and fiber-reinforced composite structure design, combines the mechanical advantages of fiber-reinforced composite materials with the electromagnetic properties of absorbing materials, realizes the high performance and multi-function of the absorbing patch, can adjust the absorbing frequency band, mechanical properties and installation convenience according to actual application requirements, has excellent environmental adaptability, processing convenience and long-term stability, and reduces the implementation cost and maintenance difficulty of electromagnetic protection measures. It is suitable for various electronic devices, such as communication equipment, radar systems, computer hardware, aerospace devices, medical equipment, etc., and can effectively reduce the electromagnetic radiation generated inside and outside the equipment, improve the electromagnetic compatibility between devices, and ensure the stable operation and information security of electronic systems.

[0026] Figure 1 FIG. 1 is a schematic diagram of the layered structure of the fiber-reinforced absorbing patch provided in an embodiment of the present invention. Figure 1 As shown, the embodiment provides a fiber-reinforced absorbing patch, including a three-layer structure: an upper absorbing patch, a middle layer of impregnated mesh fibers, and a lower absorbing patch. The middle layer of impregnated mesh fibers is used as a reinforcing matrix, and the upper and lower layers are single-layer absorbing patches. After lamination and hot pressing, a fiber-reinforced absorbing patch with a grid-like surface is made, wherein the middle layer of impregnated mesh fibers is made of a mesh cloth with through-holes made of fibers and is prepared after impregnation.

[0027] Figure 2 FIG. 1 is a schematic diagram of a method for preparing a fiber-reinforced absorbing patch according to an embodiment of the present invention. Figure 2 As shown, the embodiment also provides a method for preparing a fiber-reinforced absorbing patch, comprising the following steps: S1, preparation of microwave absorbing slurry: compound the binder and the microwave absorbing agent, wherein the added mass of the microwave absorbing agent is 80% to 90%.

[0028] S2, preparation of the intermediate layer of impregnated mesh fiber: the mesh fiber is mixed with the microwave absorbing slurry, and the impregnated mesh fiber is prepared after impregnation, rolling, blowing and curing.

[0029] S3, preparation of single-layer absorbing patch: silica gel is mixed with at least one of carbonyl iron, iron silicon chromium, iron silicon aluminum, iron nickel, cobalt-based amorphous wire, and iron-based amorphous powder, and a single-layer absorbing patch is made after casting and heat curing, and double-sided tape is attached to the back of the patch.

[0030] S4, preparation of fiber-reinforced absorbing patch: using the dipped mesh fiber as the middle layer, the upper and lower layers are single-layer absorbing patches, the single-layer absorbing patch is bonded to the middle layer of dipped mesh fiber by double-sided tape, and after lamination and hot pressing, a fiber-reinforced absorbing patch with a grid-like surface is made.

[0031] The following is combined with Examples 1-4 as Figure 4-5 The reflection loss RL curve shown in FIG. 1 and Table 1 further verify the absorbing performance and tensile strength of the fiber-reinforced absorbing patch of the present invention.

[0032] Example 1

[0033] S1, preparation of absorbing slurry: select carbonyl iron as absorber, polyurethane as binder, xylene as organic solvent, the mass ratio of carbonyl iron to polyurethane to organic solvent is 40:10:50, then add coupling agent (γ-(2,3-epoxypropoxy)propyltrimethoxysilane) and dispersant (sodium polyacrylate PMA-92), the coupling agent and dispersant are 1% and 1% of the total mass of carbonyl iron to polyurethane to organic solvent respectively, stir evenly to obtain the prepared absorbing slurry.

[0034] S2, preparation of the intermediate layer of impregnated mesh fiber: completely immerse the hexagonal mesh fabric made of polyester in the absorbing slurry prepared in S1, the thickness of the hexagonal mesh fabric is 0.35mm, and the spacing between the opposite sides is 4mm. Then put it into the vacuum equipment, vacuum impregnate for 1h, then take out the impregnated material and put it on the double roller equipment to squeeze out the excess slurry, adjust the distance between the double rollers to 0.25mm, then use a hair dryer to blow away the residual slurry, ensure that the meshes are all through holes, and then naturally air dry and solidify.

[0035] S3, preparation of single-layer absorbing patch: select carbonyl iron as the absorber, silica gel as the binder, the mass ratio of carbonyl iron to silica gel is 89:11, then add dispersant (sodium polyacrylate), defoamer (polydimethylsiloxane), inhibitor (hydroquinone), curing agent (ethylenediamine) and stir for 3 hours, wherein the amount of dispersant, defoamer, inhibitor and curing agent is 0.5%, 0.3%, 0.3% and 3% of the total mass of carbonyl iron and silica gel respectively, then put it into a vacuum equipment, evacuate and let it stand for 1 hour, then take out the slurry and put it on the casting equipment for casting, adjust the casting thickness to 0.35mm, the drying oven temperature is 120℃, bake for 10 minutes, then stick acrylic double-sided tape on the back of the dried and cured patch.

[0036] S4, preparation of fiber-reinforced absorbing patch: the dipped mesh fiber prepared by S2 is used as the middle layer, the upper and lower layers are single-layer absorbing patches prepared by S3, and the acrylic double-sided adhesive is used as the bonding layer. After lamination, hot pressing is performed on a flat vulcanizing press at a temperature of 120°C, a pressure of 20MPa, and a holding time of 20s to produce a fiber-reinforced absorbing patch with a mesh surface and a total thickness of 0.96mm. The actual sample is shown in FIG. Figure 3 shown.

[0037] S5, using the bow method of the vector network analyzer to test its reflection loss RL curve at 1-18GHz is as follows Figure 4 The tensile strength is tested by a universal mechanical testing machine, and the tensile strength is shown in Table 1.

[0038] Example 2

[0039] S1, preparation of microwave absorbing slurry: same as S1 in Example 1.

[0040] S2, preparation of the intermediate layer of impregnated mesh fiber: completely immerse the hexagonal mesh fabric made of nylon in the absorbing slurry prepared in S1, the thickness of the hexagonal mesh fabric is 0.2mm, and the spacing between the opposite sides is 2mm. Then put it into the vacuum equipment, vacuum impregnate for 1h, then take out the impregnated material and put it on the double roller equipment to squeeze out the excess slurry, adjust the distance between the double rollers to 0.1mm, then use a hair dryer to blow away the residual slurry, ensure that the meshes are all through holes, and then naturally air dry and solidify.

[0041] S3, preparation of single-layer absorbing patch: select carbonyl iron as the absorber, silica gel as the binder, the mass ratio of carbonyl iron to silica gel is 89:11, then add dispersant (sodium polyacrylate), defoamer (polydimethylsiloxane), inhibitor (hydroquinone), curing agent (ethylenediamine) and stir for 3 hours, wherein the amount of dispersant, defoamer, inhibitor and curing agent is 0.5%, 0.3%, 0.3% and 3% of the total mass of carbonyl iron and silica gel respectively, then put it into a vacuum equipment, evacuate and let it stand for 1 hour, then take out the slurry and put it on the casting equipment for casting, adjust the casting thickness to 0.5mm, the drying oven temperature is 120℃, bake for 10 minutes, then stick acrylic double-sided tape on the back of the dried and cured patch.

[0042] S4, preparation of fiber-reinforced absorbing patch: the impregnated mesh fiber prepared by S2 is used as the middle layer, the upper and lower layers are single-layer absorbing patches prepared by S3, and acrylic double-sided tape is used as the bonding layer. After lamination, hot pressing is carried out on a hot press at a temperature of 120°C, a pressure of 20 MPa, and a holding time of 20 seconds to produce a fiber-reinforced absorbing patch with a grid-like surface and a total thickness of 1.2 mm.

[0043] S5, using the bow method of the vector network analyzer to test its reflection loss RL curve at 1-18GHz is as follows Figure 5 The tensile strength is tested by a universal mechanical testing machine, and the tensile strength is shown in Table 1.

[0044] Example 3

[0045] S1, preparation of microwave absorbing slurry: same as S1 in Example 1.

[0046] S2, preparation of the intermediate layer of impregnated mesh fiber: completely immerse the stainless steel mesh fiber in the absorbing slurry prepared in S1, the mesh fiber thickness is 0.25mm, and the distance between opposite sides is 2mm. Then put it into the vacuum equipment, vacuum impregnate for 1h, then blow away the residual slurry with a hair dryer to ensure that the meshes are all through holes, and then dry naturally.

[0047] S3, preparation of single-layer absorbing patch: same as S3 in Example 2.

[0048] S4, preparation of fiber-reinforced absorbing patch: the impregnated mesh fiber prepared by S2 is used as the middle layer, the upper and lower layers are single-layer absorbing patches prepared by S3, and acrylic double-sided tape is used as the bonding layer. After lamination, hot pressing is carried out on a hot press at a temperature of 120°C, a pressure of 20 MPa, and a holding time of 20 seconds to produce a fiber-reinforced absorbing patch with a grid-like surface and a total thickness of 1.3 mm.

[0049] S5 is the same as S5 in Example 2.

[0050] Example 4

[0051] S1, preparation of microwave absorbing slurry: same as S1 in Example 1.

[0052] S2, preparation of the intermediate layer of impregnated mesh fiber: completely immerse the stainless steel mesh fiber in the absorbing slurry prepared in S1, the mesh fiber thickness is 0.12mm, and the spacing between opposite sides is 0.3mm. Then put it into the vacuum equipment, vacuum impregnate for 1h, then blow away the residual slurry with a hair dryer to ensure that the meshes are all through holes, and then dry naturally.

[0053] S3, preparation of single-layer absorbing patch: same as S3 in Example 2.

[0054] S4, preparation of fiber-reinforced absorbing patch: the impregnated mesh fiber prepared by S2 is used as the middle layer, the upper and lower layers are single-layer absorbing patches prepared by S3, and acrylic double-sided tape is used as the bonding layer. After lamination, hot pressing is carried out on a hot press at a temperature of 120°C, a pressure of 20 MPa, and a holding time of 20 seconds to produce a fiber-reinforced absorbing patch with a grid-like surface and a total thickness of 1.2 mm.

[0055] S5 is the same as S5 in Example 2.

[0056] Comparative Example 1 S1, preparation of single-layer absorbing patch: select carbonyl iron as absorber, silica gel as binder, the mass ratio of carbonyl iron to silica gel is 83:17, then add dispersant (sodium polyacrylate), defoamer (polydimethylsiloxane), inhibitor (hydroquinone), curing agent (ethylenediamine) and stir for 3 hours, wherein the amount of dispersant, defoamer, inhibitor and curing agent is 0.5%, 0.3%, 0.3% and 3% of the total mass of carbonyl iron and silica gel respectively, then put it into vacuum equipment, evacuate and let it stand for 1 hour, then take out the slurry and put it on the casting equipment for casting, adjust the casting thickness to 0.45mm, the drying oven temperature is 120℃, bake for 10 minutes, then stick acrylic double-sided tape on the back of the dried and cured patch.

[0057] S2, preparation of double-layer absorbing patch: The upper and lower single-layer absorbing patches prepared in S1 are laminated with acrylic double-sided tape as the bonding layer and then hot-pressed on a hot press at a temperature of 120°C, a pressure of 20 MPa, and a holding time of 20 seconds to form a double-layer absorbing patch with a total thickness of 1 mm.

[0058] S3 is the same as S5 in Example 1.

[0059] Comparative Example 2 S1, preparation of single-layer absorbing patch: select carbonyl iron as the absorber, silica gel as the binder, the mass ratio of carbonyl iron to silica gel is 89:11, then add dispersant (sodium polyacrylate), defoamer (polydimethylsiloxane), inhibitor (hydroquinone), curing agent (ethylenediamine) and stir for 3 hours, wherein the amount of dispersant, defoamer, inhibitor and curing agent is 0.5%, 0.3%, 0.3% and 3% of the total mass of carbonyl iron and silica gel respectively, then put it into a vacuum equipment, evacuate and let it stand for 1 hour, then take out the slurry and put it on the casting equipment for casting, adjust the casting thickness to 0.5mm, the drying oven temperature is 120℃, and bake for 10 minutes, then stick acrylic double-sided tape on the back of the dried and cured patch, with a total thickness of 0.5mm.

[0060] S2, using the vector network analyzer bow method to test its reflection loss RL curve at 1-18GHz is as follows Figure 5 shown.

[0061] Table 1 below shows the tensile strength test results of Examples 1, 2, 3, 4 of the present invention and Comparative Example 1. The tensile strength of the fiber-reinforced absorbing patch provided by the present invention is not less than 4 MPa.

[0062] Table 1 Tensile strength test results

[0063] The specific implementation methods described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above is only the most preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A fiber-reinforced absorbing patch, characterized in that: The absorbing patch includes a three-layer structure, with a middle layer of impregnated mesh fibers as a reinforcing matrix, and the upper and lower layers are single-layer absorbing patches. After lamination and hot pressing, a fiber-reinforced absorbing patch with a grid-like surface is made, wherein the middle layer of impregnated mesh fibers is a mesh cloth with through-holes made of fibers that is prepared after being impregnated.

2. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The intermediate layer of impregnated mesh fibers is in a cloth-like shape as a whole and has a thickness of 0.1 to 0.6 mm.

3. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The mesh shape of the intermediate layer of impregnated mesh fibers includes periodically arranged prism-shaped, triangular or hexagonal meshes, and the spacing between opposite sides of the hexagonal meshes is 0.3-5 mm.

4. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The material of the intermediate layer of dipped mesh fibers includes at least one of nylon, polyester, cotton, aramid, ultra-high molecular weight polyethylene, carbon fiber, stainless steel, nickel, and copper.

5. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The dipping material of the intermediate layer of dipping mesh fibers is a wave-absorbing slurry, which includes a binder and a wave-absorbing agent, and the added mass of the wave-absorbing agent is 80% to 90%.

6. The fiber-reinforced absorbing patch according to claim 5, characterized in that: The adhesive includes at least one of silica gel, polyurethane, epoxy resin, acrylic acid, and phenolic resin, and the absorber includes at least one of carbonyl iron, iron silicon chromium, iron silicon aluminum, iron nickel, cobalt-based amorphous wire, and iron-based amorphous powder.

7. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The meshes of the intermediate layer of rubber-dipped mesh fibers are still through holes after being dipped in rubber.

8. The fiber-reinforced absorbing patch according to claim 1, characterized in that: The single-layer absorbing patch is adhered with acrylic double-sided adhesive on the back side, and the total thickness is 0.25mm to 1.5mm.

9. A method for preparing a fiber-reinforced absorbing patch according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of microwave absorbing slurry: Compound the binder and the microwave absorbing agent, wherein the added mass of the microwave absorbing agent is 80% to 90%; Preparation of the intermediate layer of dipped mesh fiber: the mesh fiber is mixed with the microwave absorbing slurry, and then impregnated, rolled, blown and cured to form the dipped mesh fiber; Preparation of single-layer absorbing patch: silica gel is mixed with at least one of carbonyl iron, iron silicon chromium, iron silicon aluminum, iron nickel, cobalt-based amorphous wire, and iron-based amorphous powder, and a single-layer absorbing patch is made after casting and heat curing, and double-sided tape is pasted on the back of the patch; Preparation of fiber-reinforced absorbing patch: The dipped mesh fiber is used as the middle layer, and the upper and lower layers are single-layer absorbing patches. The single-layer absorbing patch is bonded to the middle layer of dipped mesh fiber through double-sided tape. After lamination and hot pressing, a fiber-reinforced absorbing patch with a grid-like surface is made.

10. Application of a fiber-reinforced absorbing patch in radar stealth, equipment electromagnetic wave absorption and anti-electronic interference, characterized in that: include: The fiber-reinforced absorbing patch described in any one of claims 1 to 8 is used for radar stealth, equipment electromagnetic wave absorption and anti-electronic interference.

Citation Information

Patent Citations

  • Flexible wave-absorbing non-woven fabric and preparation method thereof

    CN106079673A

  • Low-scattering covering for external field testing and preparation method thereof

    CN106273927A

  • Multi-layer structure wave-absorbing material and preparation method thereof

    CN109413974A

  • Broadband wave-absorbing material, broadband wave-absorbing sheet and preparation method

    CN115988861A

  • Method of manufacturing fiber-reinforced plastic sheet

    JP2017085024A

Cited By

  • Wave-absorbing material and application thereof

    CN120414097A